The PELATIHAN PENELITIAN TINDAKAN KELAS (PTK) UNTUK MENINGKATKAN PROFESIONALISME GURU MGMP BIOLOGI SMA KABUPATEN SEMARANG - Hastuti , Susanti Pudji; Priyayi, Desy Fajar; Cahyaningrum, Desti Christian; Keliat, Natalia Rosa (Magistrorum et Scholarium: Jurnal Pengabdian Masyarakat, 2023)
Interview results showed that teachers still experience difficulties in carrying out educational action research, especially in developing instruments for collecting data and analize the results. Community Service in collaboration with 35 teachers who are members of the Biology Teacher Association (MGMP) of Semarang District as partners was carried out as an effort to resolve these problems. Community Service was carried out through three stages, namely preparation, training, and evaluation. The main stage of this program was carried out in the form of training using the lecture and discussion methods which are presented in three parts. The results of the questionnaire analysis at the end of the program showed that on average the majority of answers were agreed (as much as 60.7%) to various statements indicating an increase in partners' understanding and skills regarding educational action research. Therefore, it was concluded that the PkM program implemented succeeded in increasing partners' knowledge of the basic concepts of educational action research  preparation. The training provided has also improved the skills of teachers in carrying out and writing scientific papers resulting from educational action research.